Chronic Isolation Stress Affects Central Neuroendocrine Signaling Leading to a Metabolically Active Microenvironment in a Mouse Model of Breast Cancer - Berry, Alessandra; Collacchi, Barbara; Capoccia, Sara; D'Urso, Maria Teresa; Cecchetti, Serena; Raggi, Carla; Sestili, Paola; Aricò, Eleonora; Pontecorvi, Giada; Puglisi, Rossella; Ortona, Elena; Cirulli, Francesca (Frontiers in Behavioral Neuroscience, 2021)
Social isolation is a powerful stressor capable to affect brain plasticity and function. In the case of breast cancer, previous data indicate that stressful experiences may contribute to a worse prognosis, activating neuroendocrine and metabolism pathways, although the mechanisms underlying these effects are still poorly understood. In this study we tested the hypothesis that chronic isolation stress (IS) may boost hypothalamic-pituitary-adrenal (HPA) axis activity, leading to changes in the hypothalamic expression of genes modulating both mood and metabolism in an animal model of breast cancer. This centrally activated signaling cascade would in turn affect the mammary gland microenvironment specifically targeting fat metabolism, leading to accelerated tumor onset. MMTVNeuTg female mice (a model of breast cancer developing mammary hyperplasia at 5 months of age) were either group-housed (GH) or subjected to IS from weaning until 5 months of age. At this time, half of these subjects underwent an acute restraint stress to assess corticosterone (CORT) levels, while the remaining subjects were characterized for their emotional profile in the forced swimming and saccharine preference tests. At the end of the procedures, all mice were sacrificed to assess hypothalamic expression levels of Brain-derived neurotrophic factor (Bdnf) Neuropeptide Y (NpY), Agouti-Related Peptide (AgRP) and Serum and Glucocorticoid-Regulated Protein Kinase 1 (SgK1). Leptin and adiponectin expression levels, as well as the presence of brown adipose tissue (BAT), were assessed in mammary fat pads. IS mice showed higher CORT levels following an acute stress and decreased expression of NpY, AgRP and SgK1, associated to greater behavioral despair in the forced swimming test. Furthermore, they were characterized by increased consumption of saccharine in a preference test, suggesting an enhanced hedonic profile. IS mice also showed an earlier onset of breast lumps (assessed by palpation) accompanied by elevated levels of adipokines (leptin and adiponectin) and BAT in the mammary fat pads. Overall, these data point to IS as a pervasive stressor that is able to specifically target neuronal circuits, mastered by the hypothalamus, modulating mood, stress-reactivity and energy homeostasis. The activation of such IS-driven machinery may hold main implications for the onset and maintenance of pro-tumorigenic environments.